Smile Aesthetic Evaluation on Videographs: An Intra-Rater and Inter-Rater Agreement Study - Mathias Faure-Brac; Angéline Antezack; Sebastien Melloul; Mehdi Hadj Saïd; Anne Raskin; Virginie Monnet-Corti (MDPI AG, 2022)
The aim of this study was to assess on videographs the intra- and inter-rater reproducibility of the Smile Esthetic Index (SEI) that has been previously validated on photographs. Smile videographs were obtained using a smartphone associated with the Smile Lite MDP mounted on a tripod. They were then randomized and evaluated twice consecutively at a 1-week interval by three periodontists according to the SEI based on 10 variables. Cohen's Kappa and Fleiss' Kappa tests were performed to measure intra- and inter-rater agreement. Sixty-five smile videographs of 24 men and 41 women (mean age 33 ± 11.3 years) were scored. A mean intra-rater agreement of 0.68 (0.64-0.73) was obtained, representing substantial agreement. The inter-rater agreement calculated for each variable ranged from 0.31 for the variable "absence of visible excessive gingiva" to 0.90 for the variable "absence of diastema and/or missing inter-dental papilla." Within the limits of this study, we have demonstrated that it was possible to use videographs to reproducibly evaluate an aesthetic score (SEI) previously validated on photographs.